2022
DOI: 10.3389/fphys.2022.998925
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and dendritic cell response to a period of intensified training in young healthy humans and rodents: A systematic review and meta-analysis

Abstract: Background: Intensified training coupled with sufficient recovery is required to improve athletic performance. A stress-recovery imbalance can lead to negative states of overtraining. Hormonal alterations associated with intensified training, such as blunted cortisol, may impair the immune response. Cortisol promotes the maturation and migration of dendritic cells which subsequently stimulate the T cell response. However, there are currently no clear reliable biomarkers to highlight the overtraining syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 156 publications
0
2
0
Order By: Relevance
“…A study on human exercise showed that physical activity results in the enhancement of peripheral blood DCs ( LaVoy et al, 2015a ). Furthermore, physical activity results in the upregulation of DC-associated IL-12 and MHC II expression in animal models ( Baker et al, 2022 ). A study investigating the mobilized DC subpopulation composition owing to acute aerobic physical activity found that plasmacytoid DCs are preferentially mobilized into peripheral circulation following exercise, which results in improved immune surveillance ( Brown et al, 2018 ).…”
Section: Immunitymentioning
confidence: 99%
“…A study on human exercise showed that physical activity results in the enhancement of peripheral blood DCs ( LaVoy et al, 2015a ). Furthermore, physical activity results in the upregulation of DC-associated IL-12 and MHC II expression in animal models ( Baker et al, 2022 ). A study investigating the mobilized DC subpopulation composition owing to acute aerobic physical activity found that plasmacytoid DCs are preferentially mobilized into peripheral circulation following exercise, which results in improved immune surveillance ( Brown et al, 2018 ).…”
Section: Immunitymentioning
confidence: 99%
“…It is important to consider that the immune system is complex, and intense training sensations and elevated levels of cortisol influence immune markers in diverse ways. Therefore, the variations can alter in everyone, and thus it is important to consider multiple diagnostic markers [11].…”
Section: Diagnosismentioning
confidence: 99%
“…On the other hand, exercise and training induce changes in circulating numbers of lymphocyte subsets [66]. With heavy training, the T-lymphocyte CD4+/CD8+ ratio typically decreases [67]. However, this ratio seems to be similar between athletes diagnosed with OTS and well-trained athletes [68].…”
Section: Uncovering Ots Markers: Biochemical Immunological and Hormon...mentioning
confidence: 99%